2013
DOI: 10.5812/ircmj.5138
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin C in Prevention of Preterm Premature Rupture of Membranes

Abstract: BackgroundPreterm premature rupture of membranes (PPROM) is one of the most important complications of the pregnancy and cause perinatal morbidity and mortality. History of PPROM is a risk factor of recurrent PPROM. Vitamin C plays an important role in collagen metabolism and increases resistance maintenance of the chorioamniotic membranes.ObjectivesThe aim of this study is to evaluate the role of vitamin C supplementation in prevention of PPROM in women with a positive history of PPROM.Patients and MethodsThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 16 publications
1
30
0
3
Order By: Relevance
“…However the results have been varied. [18][19][20] Therefore, a threshold value is needed to differentiate pregnant women with or without low plasma vitamin C level and to prove whether there is a relationship between low plasma vitamin C level and an increased risk of premature rupture of membranes in preterm pregnancy. This study shows that a plasma vitamin C level of 6.45 mg/L can be used as a threshold value to determine the status of a high plasma vitamin C level in preterm pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…However the results have been varied. [18][19][20] Therefore, a threshold value is needed to differentiate pregnant women with or without low plasma vitamin C level and to prove whether there is a relationship between low plasma vitamin C level and an increased risk of premature rupture of membranes in preterm pregnancy. This study shows that a plasma vitamin C level of 6.45 mg/L can be used as a threshold value to determine the status of a high plasma vitamin C level in preterm pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant relationship between vitamin C and MMP-1 serum levels in PROM (p=0,666) and normal pregnancy (p=0,201 (Pearlman,et al, 2004). KPD merupakan salah satu masalah obstetri yang sering terjadi dengan angka kejadian di dunia lebih kurang 10 % dari semua kehamilan (Ghomian, et al, 2013). Di Indonesia, kejadian KPD berkisar antara 6-10% dari semua kelahiran (Kemenkes RI, 2015).…”
Section: Background Premature Rupture Of Membranes Is Assumed To Occunclassified
“…Vitamin C juga berperan sebagai agen pereduksi radikal bebas (Bowman, et al, 2001). Ghomian, et al (2013) menyatakan bahwa KPD menurun secara signifikan pada kelompok yang di suplementasi vitamin C dibandingkan kelompok control (Ghomian, et al, 2013). Penelitian oleh Rizka, dkk (2011) menemukan tidak ada perbedaan bermakna antara kadar vitamin C serum ibu hamil dengan KPD dibandingkan dengan ibu hamil normal (Rizka, dkk, 2011).…”
Section: Background Premature Rupture Of Membranes Is Assumed To Occunclassified
“…27 Ghomian et al showed similar result that PPROM and PROM were significantly decreased significantly in the group that received 100 mg vitamin C from 14 weeks of gestational age compred to control (31.8% vs 44.7%; p<0.05 and 18.8% vs 34.4%; p<0.05). 28 Casanueva et al (2005) showed that 100 mg of Vitamin C per day was sufficient to maintain leukocyte ascorbic acid concentration at a level above 18 mg/10 8 cells, level to protect aginst PROM. 24 In addition, Simhan et al (2005) reported vitamin C usage significantly increased the gestational age at delivery, neonatal Apgar score, birth-weight, and latency period.…”
Section: Vitamin C and Prommentioning
confidence: 99%